Integration of attractive and defensive phytochemicals is unlikely to constrain chemical diversification in a perennial herb - Thosteman, Hanna Eriksdotter (The New phytologist, 2024)
© 2024 The Author(s). New Phytologist © 2024 New Phytologist Foundation.